The lights of Porto: The EU social season and its aftermath - László Andor (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2022)
The Spring of 2021 was a good season for Social Europe, with the European Commission coming forward with an Action Plan to implement the European Pillar of Social Rights, and the Portuguese Presidency of the Council staging an informal summit (i.e. a high level conference with heads of state and government) in Porto about strengthening the social dimension of the EU. In this paper, we look back to these key actions and analyse them in context, in particular to appreciate the significance of new European employment and social targets and their potential in the post-Covid decade. It also discusses the concrete aftermath of the social season under Portuguese Presidency in the second half of 2021 and into 2022.
Keywords: 330; Social Europe; Portuguese Presidency; European Pillar of Social Rights; European minimum wage; employment policy